A Decision Support System for Stakeholder Management during Different Project Phases considering Stakeholders’ Personality Types and Available Resources (The Case of Behsama Web-Based Information System) - Seyed Hossein Iranmanesh; Majid Shakhsi-Niaei; Mohammad Amin Durandish Yazdi (Journal of Information Technology Management)
A common mistake in the management of information technology projects is paying attention only to the technical issues and neglecting other areas of the project management. A critical area in information technology projects is the stakeholder management, which has been the focal point of many recent researches in the project management field. Thus, a decision support system (DSS) has been developed in this paper, consisting of a 10-stage operational process that leads to an executive plan for responding to the stakeholders’ expectations. The proposed DSS benefits from an optimization model that considers not only cost and time constraints, but also the possibility of partly fulfilling the stakeholders’ needs and expectations. The most important innovations in the development of this DSS are: considering the different phases of the project (planning, implementation and closing); and also, considering the personality types of contact persons in each stakeholder group. The proposed system has been implanted in a national IT project and the results have been presented in three categories, i.e. criteria and stakeholders, cost and time, and the results of the proposed model.